Evaluating the in vitro Cytotoxicity of Thymus vulgaris Essential Oil on MCF-7 and HeLa Cancer Cell Lines - Khalaf, Alsafa N.; Abed, Ibrahim J. (Iraqi Journal of Science, 2021)
Thyme essential oil (TEO) was extracted from dried leaves of Thymus vulgaris. The air-dried aerial parts of the plant produced 1.0% yield of TEO. The detection of this essential oil’s compounds was performed by GC-MASS. The cytotoxic activity of TEO was evaluated against two human cancer cell lines, namely HeLa (human epithelial cervical cancer) and MCF-7 (human breast carcinoma). Cells grown in 96 multi-well plates were treated with six concentrations of EO (6.25, 12.5, 25, 50, 100, 200 ppm) and incubated at 37 °C for 72 hrs. Cancer cell lines elicited various degrees of sensitivity to the cytotoxic effect of essential oil. The TEO exhibited significant differences (p≤ 0.01) between the effects of all concentrations against these two human cell lines. The results showed the highest toxicity of TEO on HeLa cell line (78.67%) and MCF-7 cell line (83.60%) at 200 ppm concentration. Also the values of half-maximal inhibitory concentration (IC50) of TEO against HeLa and MCF-7 cell lines were 34.63 and 27.66 ppm, respectively. Cells treated with the IC50 of TEO showed a significant difference (p ≤ 0.01) in p53 fold expression between HeLa cell line (4.33±0.41 folds) and MCF-7 cell line (5.10±0.32 folds). In general, a dose-dependent decrease the survival of the two cell lines was observed. In addition, MCF-7 cell line revealed higher sensitivity against TEO than HeLa cell line.